Immobilization of chitosan onto carbon nanotubes for lead removal from water - Al-Khatib, Ma'an Fahmi Rashid; Mirghani, Mohamed Elwathig Saeed; Kudssiah, Esssam Yassin; Husain, Iman A. F. (2009)
Carbon nanotubes (CNTs) are interesting materials which are being researched intensively in the past few years. Application of CNTs in water treatment with their unique properties has attracted the attention of many scientists and engineers. Moreover, manipulation of CNTs with other polymers has been done for different applications. This study describes the use of carbon nanotubes with attached Chitosan for lead removal from aqueous solution. The CNTs were functionalized with chitosan via covalent link. The immobilization was characterized by Fourier Transform Infrared Spectroscopy (FTIR) and Field Emission Scanning Electron Microscope (FESEM). The obtained nanocomposite was used as an adsorbent material for lead removal from aqueous solutions and its removal capacity was tested. The results show an optimum removal percentage (98.4%) at the center point conditions.